Haematological changes of Clarias gariepinus juveniles fed different dietary lipid (2012)
Twelve weeks feeding trial was conducted to determine the effects of different dietary lipid sources on the hematological changed in Clarias gariepinus juveniles, 6 iso-nitroginous diets were formulated at 45% CP and fed to triplicate groups of 15 juveniles. The feed contained (Palm Seed Oil (PSO), Ugwu Seed (USO), Soya Bean Oil (SBO), Almond Seed Oil (ASO), Mixture Of All the vegetable oil + the fish oil (MOA) and Cod Liver Oil (CLO) which is the control. The oils were added at 5% inclusion level respectively. Fish of mean weight 22.83+ 0.30g were fed these experimental diets in triplicate groups. The hematological analyses of fish showed that the red blood cell, white blood cell, Erythrocyte sedimentation rate (ESR), Mean cell volume (MCV), Mean cell Haemoglobin (MCH) and packed cell volume were not significantly different (p<0.05), but haemoglobin concentration and Mean cell haemologlobin concentration (MCHC) were significantly different (p>0.05). The present study showed that PSO, USO, ASO, SBO and MOA can effectively replace cod liver oil without compromising the health of African catfish, Clarias gariepinus.